Correlation of lipoprotein(a) with the extent of coronary artery disease in patients with established coronary atherosclerosis: gender differences. (May 2015) - Málek, Filip; Dvořák, Jan; Skalníková, Vladimíra; Mates, Martin; Kmoníček, Petr; Vávrová, Zlata; Neužil, Petr
Objective: To assess the gender differences in correlation lipoprotein(a) concentration with the extent of coronary artery disease in patients with established coronary artery disease. Patients and methods: Blood lipids and lipoprotein(a) concentrations were measured in 351 consecutive patients (256 men and 95 women) who underwent coronary angiography between January and May 2010, and who had established coronary atherosclerosis (angiography score >1). A modified angiographic Gensini Score was used. Results: Mean angiographic score was 19.6 in men and 15.0 in women. Men had lower mean high-density lipoprotein cholesterol level than women (1.05 vs. 1.18 mmol/l) and lower mean apolipoprotein A level (1.41 vs. 1.53 g/l). Mean lipoprotein(a) level was higher in men than women (307.1 vs. 282.7 mg/l). Significant inverse correlation between high-density lipoprotein cholesterol and apoA with angiographic score was identified in women ( r = −0.23, p = 0.028 and r = −0.26, p = 0.025), but not in men. Lipoprotein(a) level correlated significantly with angiographic score only in men ( r = 0.168, p = 0.0185). Conclusions: Gender differences were identified in patients with established coronary atherosclerosis in the relation of blood lipids and lipoprotein(a) levels with the extent of coronary artery disease.